Effect of Irradiation Distance on Tube Voltage Measurement and X-Ray Device Time Using Scintillator - All Adin Nurhuda; M. Ridha Mak'ruf; Tri Bowo Indrato; Sari Luthfiyah (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
The results of the output of the X-ray device are very important to know how much the correct value, whether it is in accordance with the arrangements made by radiology personnel or there is a difference even deviation of the value out of the arrangement. This conformity test activity needs a testing tool that is often used by BAPETEN personnel to find out how much the output value of KV, Time, Dose, Room leak, mA and mAs from an X-ray device unit. The purpose of this study was to analyze the effect of irradiation distance on tube voltage measurements and X-ray device time using Scintillators. The study used scintillator sensors to detect radiation, arduino as a programming source, bluetooth HC-05 as digital communication between hardware and PC, PC / Delphi as display. This research design is Pre-Experimental with After Only Design research type. Where the author takes data compared to standard tools then analyzes the data. The results showed the largest error at a distance of 120cm with a 90 KV setting of 43.52%. And the smallest error is at a distance of 120cm with a 50 KV setting of 0.07%.